Materials characterization of innovative composite materials for solar-driven thermochemical heat storage (THS) suitable for building application (vol 13, pg 30, 2018) - Jarimi, Hasila; Aydin, Devrim; Zhang, Yanan; Ding, Yate; Ramadan, Omar; Chen, Xiangjie; Riffat, Saffa (Oxford Univ Press, 2018)
[Abstract Not Available]